One stage process removal of filter cake using micro emulsion - Okoro, Emeka Emmanuel; Kio-Lawson, Deinpribo; Igwilo, Kevin C.; Ekeinde, Evelyn Bose (International Journal of Engineering and Technology, 2018)
Well productivity could depend greatly on a typical drilling fluid formulation for a particular formation, and to meet specification at the moment. The data used in this study includes experimental data and materials that emphasize the influence of mud formulation and the application on the formation. This study analyzed the effect of drilling fluid filter cake on the productivity of the well. It gives details of the drilling process in relation to mud activity and formulation of remedial chemicals for production enhancement. From the filtration result, it was observed that the 11.9ppg mud cake sample began to respond to the soak solution faster than the 12.3ppg mud sample. Thus using the same soak solution as a standard for comparison, the mud cake with less mud weight was able to show less resistance to the flow of the soak solution through the pores of the discs. The result emphasized the need to optimize mechanical field control equipment to reduce the size (thickness) of filter cake formed.